1971
DOI: 10.1128/aem.21.2.358-362.1971
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Infectious Multiple Drug Resistance Among Salmonella Isolated from Animals in the United States

Abstract: Salmonella cultures were obtained from outbreaks of animal disease from 37 states and 1 territory. They were screened for resistance to 11 antimicrobial drugs. Of the 1,251 strains studied, 935 were resistant to one or more of these agents. The three most common resistance patterns were ampicillin, dihydrostreptomycin, sulfamethoxypyridazine, tetracycline; ampicillin, dihydrostreptomycin, sulfamethoxypyridazine; dihydrostreptomycin, sulfamethoxypyridazine, tetracycline. Resistance transfer was demonstrated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…It would be very valuable indeed to have data relating different serological types to different animal species. The serotype Typhimurium appears to be an important horse pathogen (8,10,11); however,-other serotypes have been shown in horses and have produced disease (8, 11). Ofthe 23 serotypes reported to have been isolated from horsemeat by Schothorst and Kampelmacher (14), our investigation revealed 9 of the same serotypes, with a striking similarity in the most frequently isolated serotypes.…”
Section: Resultsmentioning
confidence: 99%
“…It would be very valuable indeed to have data relating different serological types to different animal species. The serotype Typhimurium appears to be an important horse pathogen (8,10,11); however,-other serotypes have been shown in horses and have produced disease (8, 11). Ofthe 23 serotypes reported to have been isolated from horsemeat by Schothorst and Kampelmacher (14), our investigation revealed 9 of the same serotypes, with a striking similarity in the most frequently isolated serotypes.…”
Section: Resultsmentioning
confidence: 99%
“…5 AMR in equine bacterial isolates, including MDR organisms and transfer between species, has been documented since the 1970s. [8][9][10][11][12] More recently, the ongoing significance and effects on health outcomes of this problem have been highlighted. [13][14][15] Although temporal changes in antimicrobial susceptibility, including the emergence of resistance to some agents, have been well characterised in a number of studies, [16][17][18] comparison of reported sensitivities from different locations demonstrates that there are important geographic differences between bacterial isolates from horses.…”
Section: Antimicrobial Use and The Emergence Of Amr In Equine Practicementioning
confidence: 99%
“…By the 1960s, there was significant resistance to penicillin in humans (Lowy 2003) and cases emerging in the United Kingdom and the United States of antibiotic resistance in animals (Anderson 1968). More critically, cases had begun to be documented of resistant strains crossing over between animals and humans (Pocurull and Mercer 1971). Despite this emerging threat, the belief that new antibiotics could always be developed as alternates when resistance emerged coupled with the perceived economic benefits for domestic and international trade in livestock meant that this issue went unaddressed.…”
Section: The Macrosecuritization Of Amrmentioning
confidence: 99%